Site-Specific and Country-of-Origin Labeling for Pharmaceutical Manufacturing. Issue 10 (October 2022) - Hatton, Randy C.; Leighton, Greg; Englander, Libbe
There is increasing concern about the quality of pharmaceuticals, especially generics made in Asia. Popular books and news reports have the public questioning the quality of pharmaceuticals. Recalls and import bans shake confidence in medications, particularly for active pharmaceutical ingredients and finished dosage forms made outside the United States. The Food and Drug Administration uses geography to allocate resources for manufacturing surveillance. Site of manufacturing labeling, including the country, could be linked to the facility's quality score to assess the risk of poor quality. Clinicians should advocate for legal and regulatory changes to increase the transparency of pharmaceutical manufacturing of products.